The big easy [videorecording (DVD)] - McBride, Jim, 1941-; Quaid, Dennis; Barkin, Ellen, 1954-; Beatty, Ned (Trimark Home Video, 1998)
A criminal's murder triggers a bloody gangland drug war. A saucy blend of New Orleans nightlife, romance and suspense.